1976
DOI: 10.1097/00005072-197603000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition and the Developing Cerebellar Cortex in the Rat

Abstract: Undernutrition of the newborn rats, produced during the first 3 weeks by increasing the litter size and restricting the mother's diet, resulted in reduction of the body and brain weights of the experimental animals. One group of undernourished animals showed especially severe reduction of body and cerebellar weights. These animals, on the 10th postnatal day, had an immature cerebellar cortex corresponding to that of the 7th day postnatal control animals. The external granular layer persisted in the cerebellar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The present study confirmed that undernutrition, induced by increased litter size, resulted in marked reduction of the body weights of the suckling rats, comparable to that reported by Bass et al (1970), Neville & Chase (1971, and Gopinath, Bijlani & Deo (1976). The morphologic sequelae of inadequate nutrition were manifested mainly in the neuronal cell processes and in the neuroglial elements of the undernourished rats, whereas little or no changes occurred in the perikarya of the various neurons.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study confirmed that undernutrition, induced by increased litter size, resulted in marked reduction of the body weights of the suckling rats, comparable to that reported by Bass et al (1970), Neville & Chase (1971, and Gopinath, Bijlani & Deo (1976). The morphologic sequelae of inadequate nutrition were manifested mainly in the neuronal cell processes and in the neuroglial elements of the undernourished rats, whereas little or no changes occurred in the perikarya of the various neurons.…”
Section: Discussionsupporting
confidence: 92%
“…A substantial body of experimental evidence has accumulated which indicates that undernutrition severely retards cerebellar growth. This is manifested by a reduction in cell numbers (Winick & Noble, 1966;Barnes & Altman, 1973;Patel, Balazs & Johnson, 1973;Gopinath et al, 1976), delayed enzymatic development (Persson & Sima, 1975), impaired myelination (Bass et al, 1970Hedley-Whyte & Meuser, 1971), stunting of Purkinje cell dendrites, and an overall decrease in the neuropil (Neville & Chase, 1971;Sima & Persson, 1975). The size and morphology of the perikarya of individual neurons were apparently unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…An uneven growth rate, contributing to formation of an irregular extension of the granular cell layer into the molecular layer, was considered to be the reason for formation of multiple small subdivisions in the cerebellum of a patient with vitamin B, dependency and of rats with vitamin B, deficiency [39, 42, 431. Postnatal undernutrition has also caused a reduction in size of the cerebellar vermis of suckling rats [8,191. However, the irregular lobulation seen in the cerebellar vermis of the phenylacetate-treated animals was not observed in neonatal undernourished rats [22]. The reduction (65%) and rapid drop of body weight in undernourished rats [ 3 2 , 561 was not found in the phenylacetate-treated rats (see Table 1).…”
Section: F I G 3 Midsagittal Sections Of Cerebellum In 15-day-old Ramentioning
confidence: 89%
“…Both cerebellar and retinal neurons of postnatally treated rats are vulnerable to the adverse effects of phenylacetate. Morphological changes observed in the cerebellum, retina, and optic nerve of treated animals during the fourth to twenty-first days of life consist of regional reduction in the size of cerebellar vermis lobules IV, V, VIa, and 14, 18, 19, 2 5 , 34, 401, but [14, 15,21,22,28,41,47,49, 551 have been described. Recently, whorls of membranous materials were found in the oligodendroglial cells in brains from two PKU patients and were called "PKU bodies" [451.…”
mentioning
confidence: 99%
“…The possibility that the observed changes in cerebellar mass are merely due to differences in tissue hydration can be dismissed in light of earlier observations (138) indicating that long exposure to increased gravity results in increased tissue hydration. Furthermore, while nutrition during early development affects CNS development (139) additional data seems to argue against the direct contribution of maternal undernutrition to the effect of hypergravity on the developing CNS. First, during lactation, despite lower food consumption, HG dams gained significantly more body mass than SC dams.…”
Section: Gravitransduction Within An Organismal Contextmentioning
confidence: 99%